The Bone Marrow-Derived Stromal Cells: Commitment and Regulation of Adipogenesis - Tencerova, Michaela; Kassem, Moustapha (Frontiers in Endocrinology, 2016)
Bone marrow microenvironment represents an important compartment of bone that regulates bone homeostasis and the balance between bone formation and bone resorption depending on the physiological needs of the organism. Abnormalities of bone marrow microenvironmental dynamics can lead to metabolic bone diseases. Bone marrow stromal cells (also known as skeletal or mesenchymal stem cells) (BMSC) are multipotent stem cells located within bone marrow stroma and give rise to osteoblasts and adipocytes. However, cellular and molecular mechanisms of BMSC lineage commitment to adipocytic lineage and regulation of bone marrow adipocyte formation are not fully understood. In this review, we will discuss recent findings pertaining to identification and characterization of adipocyte progenitor cells in bone marrow and the regulation of differentiation into mature adipocytes. We have also emphasized the clinical relevance of these findings.